Native Insect Pollinators and Their Effect on Sweet Gourd Production - Nancy, NP; Amin, MR; Miah, MRU; Miah, MG (Annals of Bangladesh Agriculture, 2020)
The study was conducted in the field laboratory of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during September 2016 to June 2017 to know the insect pollinators of sweet gourd, their behavior and their role on sweet gourd yield and seed quality. The study showed that ten species of insects belong to seven families in three orders (Lepidoptera, Diptera and Hymenoptera) were found as pollinator. The abundance of the pollinator species ranged from 0.1±0.1 to 2.2±0.3 per 30 sweeps. The cabbage butter fly and ant showed statistically similar and higher abundance compared to other insect pollinators. The foraging durations of the frequently abundant pollinators ranged from 16.8 ± 2.2 to 36.6 ± 4.4 S per flower and ant spent the longest duration. Insect pollination showed the highest number of fruit plant-1, yield ha-1 and seed fruit-1 both in winter and summer season compared to natural and hand pollination. Production of fruit, seed set and yield of insect pollinating plot in winter and summer seasons were 6.4 ± 0.3 and 4.8 ± 0.2 plant-1, 84.8 ± 2.7 and 62.6 ± 1.0 fruit-1, and 18.5 ± 0.8 and 16.7 ± 0.7 t ha-1, respectively. The findings indicated that the native insect pollinators increased the production of fruit, seed and yield of sweet gourd. Conserving and enhancing native insect pollinators may boost sweet gourd production in Bangladesh. Ann. Bangladesh Agric. (2019) 23(1) : 63-68